2020
DOI: 10.1080/00207160.2020.1777405
|View full text |Cite
|
Sign up to set email alerts
|

Fourth order method to compute the volume of archaeological vessels using radial sections: Pintia pottery (Spain) as a case study

Abstract: In the archaeological community there is an interest in knowing the volume of the vessels rescued in the excavations, to study, among other things, if the capacity measures were standardized. The problem is that sometimes it is not possible to check the volume physically because the piece is too delicate or too large or simply incomplete. There is a fairly widespread idea that it is sufficient to know a radial section of the vessel to reconstruct it in 3D. Then, the volume is approximated by dividing the heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Rodriguez and Hastorf, 2013). Three methods are often used to calculate the volume of archaeological pottery vessels, reconstructed or fragmented: truncated cones (Senior and Birnie, 1995), three-dimensional from a single radial section (Karasik and Smilanski, 2006;Sánchez and Cerdeño, 2014;SopenaVicién, 2006;Velasco and Celdrán, 2019;Zapassky et al, 2006) or from several radial sections (Portillo and Sanz, 2020).…”
Section: Pottery Volume Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodriguez and Hastorf, 2013). Three methods are often used to calculate the volume of archaeological pottery vessels, reconstructed or fragmented: truncated cones (Senior and Birnie, 1995), three-dimensional from a single radial section (Karasik and Smilanski, 2006;Sánchez and Cerdeño, 2014;SopenaVicién, 2006;Velasco and Celdrán, 2019;Zapassky et al, 2006) or from several radial sections (Portillo and Sanz, 2020).…”
Section: Pottery Volume Calculationmentioning
confidence: 99%
“…Computing the volume of archaeological vessels from several radial section gives an accurate approximation, given that archaeological pottery usually has deformations (Portillo and Sanz, 2020). Nevertheless, it is demonstrated that three-dimensional with a single radial section method is accurate enough to be used in prehistoric handmade pottery (the percentage deviation from the actual volume does not exceed 10% in large vessels in both methods; Velasco and Celdrán, 2019).…”
Section: Pottery Volume Calculationmentioning
confidence: 99%